The survival and cost-effectiveness analysis of adjunctive Chinese medicine therapy for patients with non-small cell lung cancer: a nationwide cohort study in Taiwan - Meng-Bin Tang; Wei-Yin Kuo; Pei-Tseng Kung; Pei-Tseng Kung; Wen-Chen Tsai (Frontiers Media S.A., 2024)
Introduction: Cancer, particularly lung cancer, is a significant global healthcare challenge. Non-Small Cell Lung Cancer (NSCLC) constitutes 85% of cases. Patients often seek alternative therapies like Chinese medicine alongside Western treatments. This study investigates the survival outcomes and cost-effectiveness of adjunctive Chinese medicine therapy for NSCLC patients in Taiwan.Methods: We utilized the National Health Insurance Research Database in a retrospective cohort study from 2000 to 2018, focusing on NSCLC patients diagnosed between 2007 and 2013. After propensity score matching 1:5 ratio, then compared patients with and without adjunctive Chinese medicine therapy. Survival outcomes, cost-effectiveness, and sensitivity analyses were conducted.Results: The study involved 43,122 NSCLC patients with 5.76% receiving adjunctive Chinese medicine. There is no significant associated between the risk of death and adjuvant Chinese medicine therapy until 181-365 days of adjuvant treatment could reduce the risk of death (HR = 0.88, 95% CI: 0.80-0.98). Cost-effectiveness analysis showed an incremental cost-effectiveness ratio of 880,908 NT$/year.Conclusion: Adjunctive Chinese medicine therapy, particularly when administered for 181-365 days, significantly reduced the mortality risk among stage IV NSCLC patients. The cost-effectiveness aligns with willingness-to-pay thresholds, indicating economic benefit.